2012
DOI: 10.4025/actasciagron.v34i3.12660
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol levels in natural and artificial aging of soybean seeds

Abstract: ABSTRACT. Tocopherols are well known constituents of vitamin E, and the main antioxidants in soybean. Are natural antioxidants and stabilizers that can inhibit lipid degradation, reducing non-enzymatic oxidation of these compounds during storage of seeds, germination and initial development of seedlings. The objective of this work was to determine the level of α-tocopherol in four soybean seeds cultivars naturally and artificially aged. Seeds of four soybean cultivars stored from 0 to 180 days in a dry chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…When seeds are subjected to severe stress there is a signifi cant increase in lipid peroxidation and the decrease in tocopherol production resulting in the defi ciency of antioxidant which is not balanced by another protective mechanism, thus causing the reduction of compounds in the seed (Giurizatto et al, 2012). This fact coincide with the observed in present study which resulted in a signifi cant antioxidant loss during storage.…”
Section: --------------------% -----------------supporting
confidence: 79%
See 2 more Smart Citations
“…When seeds are subjected to severe stress there is a signifi cant increase in lipid peroxidation and the decrease in tocopherol production resulting in the defi ciency of antioxidant which is not balanced by another protective mechanism, thus causing the reduction of compounds in the seed (Giurizatto et al, 2012). This fact coincide with the observed in present study which resulted in a signifi cant antioxidant loss during storage.…”
Section: --------------------% -----------------supporting
confidence: 79%
“…Thus, the inverse action of natural antioxidants, such as tocopherol, may occur blocking the oxygen uptake by seed tissues, protecting the polyunsaturated fatty acids from peroxidation (Giurizatto et al, 2012). In cottonseeds the tocopherol content can range from 237 to 674 mg .kg -1 , depending on the cultivar used and on the growing and storage conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous researches were performed on both artificially and naturally aging of the same seed and revealed that, for the artificially aged seed, significant declination occurs compared to seeds in conventional storage conditions. The amount of α-tocopherol (an antioxidant that blocks the entrance of oxygen into the internal tissue of seed which causes deterioration) was present in high amounts in artificially aged seeds compared to naturally aged seeds where the experiment was done on four types of soybean cultivars [ 17 ]. Petruzzelli and Carella [ 18 ] conducted a research in 1983 on artificial and natural aged wheat seed and proved that artificially aging of seed amplifies the deteriorative changes for seed than naturally aging.…”
Section: Introductionmentioning
confidence: 99%
“…Non-enzymatic mechanisms include SSPs and low molecular weight antioxidants such as tocopherol (vitamin E), ascorbate, and glutathione etc. ( Sattler et al, 2004 ; Giurizatto et al, 2012 ; Sano et al, 2016 ). Arabidopsis VTE1 (a limiting factor in tocopherol biosynthesis), AtTIL (a temperature-induced lipocalin), and AtCHL (a chloroplastic lipocalin) are involved in lipid protection during seed aging ( Havaux et al, 2005 ; Boca et al, 2014 ; Nguyen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%